Molecular Docking and ADMET Profiling of Vitex negundo Phytoconstituents Targeting Inflammatory Proteins in Rheumatoid Arthritis: Research Article (Journal of Pharma Insights and Research, 2025)
A computational study of bioactive compounds from Vitex negundo showed significant binding interactions with crucial protein targets involved in rheumatoid arthritis (RA) pathogenesis. Molecular docking studies using PyRx and Biovia Discovery Studio evaluated the binding affinities of vitexin, ursolic acid, oleanolic acid, and tris(2,4-di-tert-butyl) phosphate against NF-κB, TLR4, JNK, and sPLA2. The docking analysis demonstrated notable binding energies, with vitexin exhibiting the strongest affinity (-8.7 kcal/mol) toward NF-κB, followed by ursolic acid-TLR4 complex (-8.5 kcal/mol). Detailed interaction analysis showed stable conformations supported by hydrogen bonding, hydrophobic interactions, and metal coordination, particularly in the vitexin-NF-κB complex involving LEU19, CYS5, and zinc ion coordination. SwissADME evaluation confirmed favorable drug-likeness properties and ADME characteristics of the compounds. The molecular-level interactions and pharmacokinetic predictions indicate the therapeutic potential of Vitex negundo phytoconstituents as multi-target agents for RA treatment.